The Effect of Risk Management in Improving Portfolio Performance on LQ45 Stocks in the Indonesian Capital Market - Rahayu, Putri; Lestari P.A., Diana Indah Sri; R. Pandin, Maria Yovita (Jurnal Ilmiah Ekonomi Global Masa Kini, 2024)
This study aims to analyze the effect of risk management on the performance of the LQ45 stock portfolio in the Indonesian capital market, which consists of large-cap and high-liquidity stocks. The stocks in this index have a special attraction for institutional and individual investors due to their higher stability compared to other stocks on the Indonesia Stock Exchange (IDX). However, they remain vulnerable to various market risks, including changes in macroeconomic conditions, government policies, and fluctuations in global sentiment. This study uses secondary data from the financial statements of LQ45 companies over a certain period and conducts multiple linear regression analysis of risk management variables, such as Price-to-Earnings Ratio (PER), Beta Portfolio, Dividend Yield, and Market Capitalization. The results show that these variables do not have a significant influence on portfolio performance, as indicated by the coefficient of determination of 11.8%, which indicates that most of the variation in portfolio performance (88.2%) is influenced by factors outside the model. Portfolio beta theoretically shows the greatest potential influence, but the statistical results are not significant. The study concludes that while risk management plays an important role in maintaining portfolio stability, a more comprehensive approach is needed to optimize investment returns. Portfolio diversification strategies, proper asset allocation, and analysis of global market trends are important in the face of Indonesian capital market volatility. This study contributes to the portfolio management literature in Indonesia by offering practical guidance for investors to develop effective investment strategies to manage risk and maximize their portfolio returns amidst complex and volatile market dynamics. Keywords: Risk Management, Portofolio Performance, LQ45 Stocks, Capital Market